Exposure to nano-polystyrene induces metabolic alteration in lipid homeostasis in Caco-2. Issue 5 (20th April 2021) - Kim, Sun Jo; Long, Nguyen Phuoc; Jung, Cheol Woon; Anh, Nguyen Hoang; Min, Jung Eun; Kim, Hyung Min; Kwon, Sung Won
Abstract : Disturbance in lipid homeostasis was revealed by global metabolic profiling following acute and prolonged exposure to 50 nm polystyrene. Abstract : Nano-polystyrene has gained considerable attention because of its growing accumulation in the environment. Although several studies have attempted to elucidate its action on physiological functions, studies investigating human metabolic disturbance were scarce. This study developed two investigative designs using exposure to human epithelial colorectal cells (Caco-2); the first exposed cells to a high concentration of 50 nm nano-polystyrene for 24 h (acute), whilst the second exposed cells to a relatively lower concentration for over 1.5 months (chronic). Exposure concentrations were determined based on bioassays: 10 and 80 μg mL −1 for the acute model and 0.1 μg mL −1 for the chronic exposure model. Following acute exposure, untargeted metabolic profiling revealed the alteration in lipid metabolic pathways, including steroid and arachidonic acid metabolism. On the other hand, chronic exposure induced relatively minor disturbances. However, there was still a potential effect on fatty acid biosynthesis, indicating that acute and chronic exposure to nano-polystyrene may disturb lipid homeostasis. We also confirmed changes in the expression levels of lipid transcriptional regulatory factor coding genes, namely sterol regulatory element-binding transcription factors 1 and 2. The total fatty acid composition was further investigated to verify metabolic disturbance by chronic exposure. Our findings indicated that both exposure conditions of high concentration with a short period and low concentration with an extended period to nano-polystyrene were associated with the cellular disturbance of the lipid metabolism.